A remarkable new genus of Sciomyzoidea from Japan, with discussion of its taxonomic position (Diptera, Acalyptratae) - Saigusa, Toyohei (Zootaxa, 2024)
An acalyptrate fly, Babakintaromyia albitarsis gen. et sp. nov., of the superfamily Sciomyzoidea is described from Japan. Wing venation is similar to that of the sciomyzid genus Salticella Robineau-Desvoidy, but the species differs abundantly from Salticella in other respects. Taxonomic characters of the new species differ from those of most or all species of Sciomyzidae in some important ways, including the absence of a preapical dorsal seta on all tibiae. The new genus is tentatively assigned to the subfamily Salticellinae of the Sciomyzidae.